BARRIERS TO ONLINE ENGLISH LEARNING AMONG SECONDARY STUDENTS DURING THE COVID-19 PANDEMIC IN INDONESIA - Tanasal, Amanda Amelia; Munir, Munir; Aeni, Nur (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This study aims to explore the barriers faced by Indonesian secondary education students in learning English through online platforms during the COVID-19 outbreak. Employing a qualitative descriptive approach, data were gathered through semi-structured interviews with five students from SMA Negeri 13 Makassar using a snowball sampling technique. The findings reveal seven key barriers: lack of clear instruction and limited teacher engagement, excessive assignment loads with minimal explanation, limited digital literacy among students and teachers, unstable internet connectivity, poor communication and delayed teacher responses, low student motivation, including psychological and emotional challenges, and an unsupportive home learning environment. These interrelated barriers significantly hindered students' ability to engage meaningfully in online English learning. The study highlights the importance of clear instructional design, digital competence, consistent communication, and supportive learning environments in ensuring effective online education. The findings are expected to inform future educational strategies and policies for more equitable and accessible English language learning, especially during times of crisis.